2009
DOI: 10.1080/14767050903198132
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic closure of the ductus arteriosus: Benefits and limitations

Abstract: Patency of the ductus arteriosus (PDA), a common complication of preterm birth, has been associated to increased risk for intraventricular cerebral hemorrhage, necrotizing enterocolitis, bronchopulmonary dysplasia and death. Consequently, prophylactic or curative treatment has been advocated before the critical left-to-right shunting occurs. A host of studies has shown that both pharmacological agents and surgical closure are effective in closing the ductus arteriosus in premature infants. Indomethacin has lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…The small number of patients ( n = 27) might have limited the power to detect a true effect. It is also possible that confounding factors were reflected this way, since those newborns had a very low body weight, (mean 852 g, range 440–1390 g), as well as haemodynamically significant PDA, which is associated with poor renal perfusion . Even so, PDA had no significant impact on CL per se in this analysis.…”
Section: Discussionmentioning
confidence: 94%
“…The small number of patients ( n = 27) might have limited the power to detect a true effect. It is also possible that confounding factors were reflected this way, since those newborns had a very low body weight, (mean 852 g, range 440–1390 g), as well as haemodynamically significant PDA, which is associated with poor renal perfusion . Even so, PDA had no significant impact on CL per se in this analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Low diastolic blood pressure values associated with the diastolic theft revealed by transfontanellar ultrasound in an extremely low birth weight premature newborn, without clinical evidence of ductal dependent cardiac malformation, raised the suspicion of a persistent ductus arteriosus. Taking into account the increased frequency of patent ductus arteriosus in extremely low birth weight premature newborns, as revealed by other studies [4,5], coupled with a respiratory tract infection, pathology common in infants with this malformation [4], initiation of cyclooxygenase inhibitor therapy was decided. Due to reduced renal side effects compared to other drugs, ibuprofen in three consecutive doses is administrated.…”
Section: Discussionmentioning
confidence: 99%
“…Patent ductus arteriosus is a common pathology in extremely low birth weight premature newborns, being identified in 80% of cases. This increases the risk of developing intraventricular haemorrhage, necrotic ulcerative enterocolitis, or chronic lung disease [5]. Clinical diagnosis of patent ductus arteriosus in the premature new-born weighing less than 1000 grams represents a challenge, given the association with respiratory distress syndrome by surfactant deficiency [3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these side effects of indomethacin, another cyclooxigenase inhibitor, a derivative of ibufenac, ibuprofen, emerged. A large number of randomized studies comparing the two drugs showed the same efficacy for the closure of the patent ductus aretriosus [162,163]. Moreover, the use of ibuprofen has demonstrated fewer side effects on the renal, mesenteric and cerebral blood flows [164].…”
Section: Nsaidsmentioning
confidence: 99%